Analisis Faktor-Faktor dalam Meningkatkan Kinerja Karyawan pada Koperasi Perkebunan Sawit (KPS) Maju Pirbun Pasaman Barat - Riyana Octavalia; Fajar Budiman; Maisarah Leli (Universitas 17 Agustus 1945 Semarang, 2024)
Every company, whether public or corporate, is established to achieve certain goals. To achieve success, the foundation of competence needs to be considered. Factors are useful to help organizations improve performance. To support the performance of an employee, employees are needed who have performance factors in accordance with the needs needed in a company. This study aims to determine the factors of employee performance seen from indicators of performance knowledge, motivation, organizational culture of the performance of employees of the advanced palm oil plantation cooperative Pirbun West Pasaman in carrying out their duties or work. The research motede used is a qualitative method, data collection techniques are interviews, observations, and document studies. The results of this study obtained the conclusion that the performance factors of employees in the advanced palm oil plantation cooperative (KPS) advanced pirbun pasaman barat are adequate. This can be seen based on indicators put forward by Spencer, namely performance knowledge, motivation, employee performance organizational culture. each of these indicators has been fulfilled in the employees of the advanced palm oil plantation cooperative (KPS) pirbun west pasaman.